Spectral Characteristics of Greenland Lichens - Van Der Veen, Cornelis; Csatho, Bea (Géographie physique et Quaternaire, 2005)
AbstractSpectral reflectance measurements conducted during two field campaigns in west Greenland, and in the laboratory using samples collected during those campaigns, are discussed to evaluate the spectral signature of lichens. Given the diversity in lichen species, colors, and appearance — ranging from crust-like (crustose) to almost like mini shrubs (fructicose) — it is not surprising that no single signature was found. Some of the brighter fructicose lichens have reflectance characteristics very similar to those of green vegetation, with a pronounced rise in reflectivity around 750 nm. However, the most abundant lichen species covering rocks in the ice-marginal zone of west Greenland are dark grey to black crustose and foliose ephilithic (rock-growing) lichens and the shape of the reflectance spectrum for these lichens is generally very different from that of other surface types and landcovers, with near-zero reflectance at visible wavelengths, and a maximum around 1 600 nm. This characteristic allows rock-covered lichen to be identified on multispectral satellite imagery.